Influence of oil and gas emissions on summertime ozone in the Colorado Northern Front Range. Issue 14 (23rd July 2016) - McDuffie, Erin E.; Edwards, Peter M.; Gilman, Jessica B.; Lerner, Brian M.; Dubé, William P.; Trainer, Michael; Wolfe, Daniel E.; Angevine, Wayne M.; deGouw, Joost; Williams, Eric J.; Tevlin, Alex G.; Murphy, Jennifer G.; et al.
Abstract: Tropospheric O3 has been decreasing across much of the eastern U.S. but has remained steady or even increased in some western regions. Recent increases in VOC and NOx emissions associated with the production of oil and natural gas (O&NG) may contribute to this trend in some areas. The Northern Front Range of Colorado has regularly exceeded O3 air quality standards during summertime in recent years. This region has VOC emissions from a rapidly developing O&NG basin and low concentrations of biogenic VOC in close proximity to urban‐Denver NOx emissions. Here VOC OH reactivity (OHR), O3 production efficiency (OPE), and an observationally constrained box model are used to quantify the influence of O&NG emissions on regional summertime O3 production. Analyses are based on measurements acquired over two summers at a central location within the Northern Front Range that lies between major regional O&NG and urban emission sectors. Observational analyses suggest that mixing obscures any OPE differences in air primarily influenced by O&NG or urban emission sector. The box model confirms relatively modest OPE differences that are within the uncertainties of the field observations. Box model results also indicate that maximum O3 at the measurement location is sensitive to changes in NOx mixing ratio but also responsive to O&NG VOC reductions. Combined, these analyses show that O&NG alkanes contribute over 80% to the observed carbon mixing ratio, roughly 50% to the regional VOC OHR, and approximately 20% to regional photochemical O3 production. Key Points: Modeled photochemical O3 production is Nox ‐sensitive at a central location in the Colorado Northern Front Range Oil and natural gas VOC emissions contribute over 80% to the observed carbon mixing ratio and 17.4% to maximum modeled photochemical O3 Observed O3 production efficiencies are variable but show an influence of less than 1.8 ppbv/ppbv from oil and natural gas VOC emissions